Laparoscopic Management of Bouveret's Syndrome after Failed Endoscopic Approach. (18th April 2019) - Tchercansky, Ariel Nicolas; Busnelli, Guido Luis; Mihura, Matías; Maurette, Rafael José
Abstract : Bouveret's syndrome is a complication of cholelithiasis that presents with gastric outlet obstruction due to an impacted gallstone in the duodenum following cholecystoduodenal fistula. This is a rare presentation of biliary-enteric fistula; therefore, there are no standardized guidelines for the management of this disease. We present a case of a patient with Bouveret's syndrome managed with laparoscopic surgery after an unsuccessful attempt of endoscopic removal.